Depth-Wise Distribution of Boron in Soil Under Groundnut- Cabbage Cropping Sequence - Bhavin Suthar; Dileep Kumar; K.C. Patel; A.K. Shukla; Sanjib Kumar Behera; J.C. Shroff; R.A. Patel (Journal of the Indian Society of Soil Science, 2024)
B application schedues in groundnut-cabbage cropping system, conducted during the year 2014-2015 to 2019-2020 at Anand Agricultural University, Anand, Gujarat, India. The surface as well as sub-surface soil samples (0-15, 15-30, 30-45, 45-60, 60-75 cm) were collected from each plot. The treatments involving combinations of three B application frequencies (application only in the first year, alternate year and every year) and four B application rate (0.5, 1.0, 1.5 and 2.0 kg B ha-1) with a total treatment combinations of 13 including one control. The B was applied to the soil as borax to groundnut crop only. The effects of B application schedules on B fractions, i.e., readily soluble B, specifically adsorbed B, oxide bound B, organically bound B and residual B were significant under different soil depths. The amount of B fractions was increased with the level of B application. The surface soil (0-15 cm) had the greatest B concentration across all fractions, and the amount of B applied. While the residual B fraction increased with soil depth, and the readily soluble B, particularly adsorbed B and oxide bound B fractions dropped.